2021
DOI: 10.31557/apjcp.2021.22.12.4057
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Cancer Stem Cell Markers in Cervical Cancer: A Systematic Review and Meta-Analysis

Abstract: Cervical cancer is the fourth most common type of gynecological cancer worldwide (Pimple et al., 2016). Most cervical cancer is caused by human papillomavirus (HPV) infection (Hashiguchi et al., 2019). There were 528,000 new cases every year, with 266,000 deaths in 2012 worldwide. In developing countries, cervical cancer also has high mortality rates among women (Pimple et al., 2016). There were 14,480 new cases in the United States in 2021 (American Cancer Society, 2021). ( American Cancer Society, 2021). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…CD44 expression in cancer has been correlated with both poor and favourable outcomes [49]; however, growing evidence now suggests that overexpression of CD44 and its isoforms is an unfavourable prognostic indicator in cancer patients [50][51][52][53][54][55][56][57][58][59][60][61]. A list of some of these studies, although not comprehensive, is provided in Table 1.…”
Section: Expression Of Cd44 As a Prognostic Biomarkermentioning
confidence: 99%
“…CD44 expression in cancer has been correlated with both poor and favourable outcomes [49]; however, growing evidence now suggests that overexpression of CD44 and its isoforms is an unfavourable prognostic indicator in cancer patients [50][51][52][53][54][55][56][57][58][59][60][61]. A list of some of these studies, although not comprehensive, is provided in Table 1.…”
Section: Expression Of Cd44 As a Prognostic Biomarkermentioning
confidence: 99%
“…Importantly, studies conducted on the HeLa cell line showed that natural polyphenols such as karanjin, plumbagin, and pongapin, which affect the inhibition of cell proliferation and induce apoptosis, also have the ability to attenuate the expression of the HA-CD44 pathway [55]. The important role of HA in the course of cancer is indicated by a meta-analysis of 22 studies from electronic databases involving more than 2200 patients with CC [82]. In the studied group of women, a correlation was determined between the expression levels of seven important CSC markers, including the CD44 protein, and clinical parameters DFS and OS [82].…”
Section: Cervical Cancermentioning
confidence: 99%
“…The important role of HA in the course of cancer is indicated by a meta-analysis of 22 studies from electronic databases involving more than 2200 patients with CC [82]. In the studied group of women, a correlation was determined between the expression levels of seven important CSC markers, including the CD44 protein, and clinical parameters DFS and OS [82]. Specifically, it was shown that overexpression of CD44, a major cell surface receptor for hyaluronan, was significantly associated with worse OS (HR 1.14, 95% CI 1.07-1.22, p = 0.0001) [82], suggesting that this marker could be used as a prognostic indicator of adverse survival among CC patients.…”
Section: Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of advanced cervical cancer includes surgery, chemotherapy, and radiation therapy, but cervical cancer mortality remains high ( 141 ), mainly related to CSCs ( 142 ). Studies have suggested that ALDH1 can be used as a cervical CSC marker ( 143 , 144 ), which can lead to resistance to chemotherapy and is closely related to a poor prognosis ( 145 ).…”
Section: Aldh1 and Various Solid Tumorsmentioning
confidence: 99%